The Influence of Serum Lactate Dehydrogenase and Lactic Acid Levels on the Occurrence and Progression of Osteoporosis - Bai, Lei; Jia, Jingkun; Miao, Zukang; Pei, Zhiwei; Zhang, Hongjie; Yang, Hongwei; Ma, Jianxiong; Ma, Xinlong (Journal of Contemporary Medical Practice, 2025)
Objective: By collecting and analyzing serum lactate dehydrogenase (LDH) and lactic acid levels in patients with osteoporosis, and comparing them with other common biochemical indicators used in osteoporosis diagnosis, this study aims to explore the impact of serum LDH and lactic acid levels on the occurrence and progression of osteoporosis, further clarify their relationship with osteoporosis, and provide new clinical evidence for the scientific prevention and treatment of osteoporosis. Methods: A retrospective analysis was conducted on 150 patients who underwent bone mineral density (BMD) measurement at the Bone Density Room of Tianjin Hospital from June 2024 to December 2024. Based on BMD T-scores, the patients were divided into three groups: normal bone mass, osteopenia, and osteoporosis, with 50 cases in each group. General data of the three groups, including name, gender, age, weight, height, BMI, serum LDH, lactic acid, and other related clinical biochemical indicators [alkaline phosphatase (ALP), serum calcium, serum phosphorus, uric acid, urine creatinine, cystatin C, P1NP, β-CTx were collected from the Clinical Laboratory of Tianjin Hospital. The correlation and degree of correlation between serum LDH, lactic acid and BMD T-scores were analyzed and compared with other clinical biochemical indicators. Differences within and between groups were also compared to comprehensively evaluate the impact of serum LDH, lactic acid levels, and other biochemical indicators on the occurrence and progression of osteoporosis. All clinical data collected in this study were approved by the Ethics Review Committee of Tianjin Hospital, complying with ethical requirements. Results: Comparative analysis showed that there was a significant negative correlation between serum LDH and BMD T-scores in 150 patients (correlation coefficient: -0.669), indicating that higher serum LDH levels were associated with lower BMD T-scores and more severe osteoporosis. In contrast, lactic acid levels showed a significant positive correlation with BMD T-scores (correlation coefficient: 0.732), meaning higher lactic acid levels were associated with higher BMD T-scores and milder osteoporosis. Comprehensive comparison of the correlation between other biochemical indicators and BMD T-scores revealed that serum calcium, serum phosphorus, and urine creatinine had a certain positive correlation with BMD T-scores, i.e., higher levels of these indicators were associated with higher BMD T-scores and milder osteoporosis. Conclusion: Serum LDH and lactic acid, as clinical biochemical markers, are significantly correlated with BMD T-scores. LDH is negatively correlated with BMD T-scores, while lactic acid is positively correlated with BMD T-scores. These two indicators have a significant impact on the occurrence and progression of osteoporosis. The conclusions of this study are expected to better guide the diagnosis and treatment of osteoporosis and provide more scientific basis for clinical decision-making.